Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1248/bpb.b17-00622
|View full text |Cite
|
Sign up to set email alerts
|

Role of Supplementary Selenium on the Induction of Insulin Resistance and Oxidative Stress in NSY Mice Fed a High Fat Diet

Abstract: The role of supplementary selenium on the induction of insulin resistance and oxidative stress in a diabetic mouse model was investigated in NSY mice on a high fat diet (HFD) and administered seleno-L-methionine (SeMet)-containing water for 12 weeks. Significant increases in oral glucose tolerance-tested (OGTT), insulin tolerance-tested, and non-fasting blood glucose levels were observed in mice on a HFD, as well as the significant increases in OGTT and non-fasting plasma insulin levels. Mice on a HFD had decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In our analysis, only markers of insulin resistance (insulin concentration and HOMA-IR), but not glucose, were associated with selenium in the fully adjusted model. Our findings corroborate the hypothesis that high selenium status disturbs insulin metabolism leading to hyperinsulinemia ( 27 , 28 ), but the effect on glucose is not as strong, as it can be mitigated when controlling strong risk factors for T2DM such as body weight and metabolic syndrome. In our study, no association between selenium status and the prevalence of diabetes was observed, which counteracts the findings reported in two other studies conducted in the NHANES population ( 18 , 29 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our analysis, only markers of insulin resistance (insulin concentration and HOMA-IR), but not glucose, were associated with selenium in the fully adjusted model. Our findings corroborate the hypothesis that high selenium status disturbs insulin metabolism leading to hyperinsulinemia ( 27 , 28 ), but the effect on glucose is not as strong, as it can be mitigated when controlling strong risk factors for T2DM such as body weight and metabolic syndrome. In our study, no association between selenium status and the prevalence of diabetes was observed, which counteracts the findings reported in two other studies conducted in the NHANES population ( 18 , 29 ).…”
Section: Discussionsupporting
confidence: 87%
“…These studies have associated the upregulation of the selenoproteins glutathione peroxidase 1 (GPX1), methionine sulfoxide reductase B1 (MSRB1), selenoprotein S (SELENOS) ( 27 ) and selenoprotein P (SELENOP) ( 30 ) induced by high selenium intake with hyperglycaemia, decreased insulin sensitivity and liver triglyceride concentrations. It was hypothesized that increased synthesis of these antioxidant selenoproteins diminishes intracellular reactive oxygen species derived from glucose metabolism and disturbs key regulators of pancreatic beta-cells, leading to chronic hyperinsulinaemia ( 27 , 28 ). An experimental animal model of diabetes revealed that neutralization of SELENOP improved glucose tolerance and insulin secretion ( 31 ), suggesting that this selenoprotein may play a particularly important role in the pathogenesis of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma adiponectin showed a minor increase in association with HFD induced obesity (chow ad libitum vs. HFD ad libitum ; Figure 3C), which is at variance to most, but not all reports from the literature [e.g. (3336)], and which was reversed with amelioration of obesity by hypoxia or restricted feeding (Figure 3C). Obesity distinctly increased plasma FGF-21 (chow ad libitum vs. HFD ad libitum ; Figure 3D), which showed a trend toward higher concentrations under exposure to hypoxia than under food restriction (pmol/l: hypoxia, 44.1 ± 9.5, vs. weight matched control, 23.7 ± 3.6; p = 0.058; Figure 3D).…”
Section: Resultssupporting
confidence: 59%
“…MDA levels were 0.018±0.005 nmol/g protein for O group; 0.016±0.005 nmol/g protein for N group; 0.01±0.005 nmol/g protein for L group for spleen and 0.031±0.004 nmol/g protein for O group; 0.02±0.004 nmol/g protein for N group; 0.017±0.004 nmol/g protein for L group for liver. This study was based on the premise that a hypercaloric diet induce oxidative stress in rats causing hepatic steatosis and cellular hypertrophy as shown in previous studies [34,35]. Our working hypothesis was that PLGA NP's loaded with lutein increase the antioxidant defenses due to lutein antioxidant potential [25].…”
Section: Resultsmentioning
confidence: 97%